Labour Wages, Fringe Benefit as Hedonic Motivation for Employee Workplace Behaviour in Corporate Establishment - Chidiebere U. Enukoha; Pius U. Angioha; Mary U. Ojong-Ejoh (PT Mattawang Mediatama Solution, 2022)
The study assessed labour wages, fringe benefits as hedonic motivation for employee workplace behaviour. Adopting a descriptive and quantitative approach, the survey method was adopted to collect data from 436 participants from a population of 736 staff of eight selected commercial banks in cross river state, Nigeria using the purposive, proportional and simple random sampling. The instrument of data collection is the self-developed and administered questionnaire, designed in a four-point format. Data collected was analyzed using descriptive and parametric statistics. Result revealed that 72.2 per cent of bank employees believe that a good wage will improve productivity, 95.2 per cent reported that a good performance deserves good pay. All employees interviewed reported being paid overtime. 89.9 per cent reported that they go on paid leave. From the parametric analysis carried out, a significant correlation exists between labour wages, fringe benefits and employee workplace behaviour. The study recommends, amongst others, that bank management need to review their compensation packages